2018
DOI: 10.1177/2056305118765740
|View full text |Cite
|
Sign up to set email alerts
|

Digitally Mediated Protest: Social Media Affordances for Collective Identity Construction

Abstract: Many scholars discuss the role of social media in the context of social movements, but there remain major disagreements regarding the precise role that social media plays. One area that deserves more in-depth study is the affordances of social media for constructing collective identity. This article examines the case of an Iranian women's rights campaign page on Facebook, "My Stealthy Freedom," using an analysis of textual and visual content. The article examines how online campaign pages on Facebook contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 69 publications
0
63
0
2
Order By: Relevance
“…As such, organizational studies typically investigate how affordances enable collective and collaborative behaviors that were difficult or impossible to achieve in combination before the emergence of these new technologies (Treem and Leonardi, 2012). Similarly, SM research has identified collective affordances through which activists and SM organizations symbolically construct a collective identity (Khazraee and Novak, 2018), as well as exchange organizational roles while depending on each other’s contributions (Vaast et al, 2017). Overall, recent research in both SM and organization studies that examines individual and collective levels has found various social media affordances that support key aspects of collective action (see Sæbø et al, 2020 for a review).…”
Section: Social Media Affordances and Collective Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, organizational studies typically investigate how affordances enable collective and collaborative behaviors that were difficult or impossible to achieve in combination before the emergence of these new technologies (Treem and Leonardi, 2012). Similarly, SM research has identified collective affordances through which activists and SM organizations symbolically construct a collective identity (Khazraee and Novak, 2018), as well as exchange organizational roles while depending on each other’s contributions (Vaast et al, 2017). Overall, recent research in both SM and organization studies that examines individual and collective levels has found various social media affordances that support key aspects of collective action (see Sæbø et al, 2020 for a review).…”
Section: Social Media Affordances and Collective Actionmentioning
confidence: 99%
“…Celebratory accounts of the Arab Spring uprisings, and the Occupy and Indignados movements, often focus on affordances, that is, “the action possibilities and opportunities that emerge from actors engaging with [social media] technologies” (Faraj and Azad, 2012: 238). While affordances, such as instantaneous and reciprocal communication, are important to the emancipatory and organizing potential of social media (Khazraee and Novak, 2018), they are merely one part of a much bigger picture (Uldam and Kaun, 2019). Indeed, recently SM scholars have argued that the commercial orientation of corporations that own social media might not always accommodate activists and may work against their intended goals (Coretti and Pica, 2018; Poell and Van Dijck, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Soft determinism recognizes that while technology has features that may constrain and enable how people use them, users are creative and will likely use these technologies in a variety of ways, including those not envisioned by designers or producers (Howard, 2011). Communicative affordances refer to those specific to communication technologies (Hutchby, 2001;Khazraee and Novak, 2018;Schrock, 2015), such as how they enable sociality (Wellman et al, 2001), connectivity and the creation of affective news streams and publics (Papacharissi, 2015(Papacharissi, , 2016. Affordances are collective when people use a (communication) technology for personal needs, but that are shared and in the aggregate manifest in collective outcomes (Vaast et al, 2017).…”
Section: Cultural Affordancesmentioning
confidence: 99%
“…Solidaritas memberi para pelaku gerakan suatu kemampuan untuk memahami keberadaan mereka secara bersama. Melucci mengartikan solidaritas sebagai yaitu kemampuan dari aktor untuk mengakui dan diakui oleh orang lainnya, karena memiliki unit sosial yang sama (Melucci, 1996;Khazraee and Novak, 2018). Solidaritas memberi tenaga bagi identitas kolektif (Melucci, 1996).…”
Section: Pengkonstruksian Identitas Kolektif Adat Bali Dalam Gerakan Btrunclassified
“…Dengan reformulasi nilai-nilai dan norma-norma, bingkai diskursif menguatkan identitas kolektif dan mencegah konflik-konflik internal yang dapat merusak persatuan(Melucci, 19Ketiga, aksi dari gabungan desa adat tersebut diberitakan secara meluas oleh kelompok media Bali Post di Bali dan juga disebarkan luaskan melalui media sosial para penggiat dan pendukung gerakan BTR. Kampanye gerakan melalui media massa dan media sosial telah berkontribusi pada formasi identitas kolektif dan membantu mengkonstruksi narasi dalam gerakan(Khazraee and Novak, 2018). Aksi kolektif tersebut menarik perhatian dari prajuru-prajuru dari desa-desa adat lainnya.Seperti yang dinyatakan oleh subjek WST dan KT dari Desa AdatPasedahan.…”
unclassified